Analysis of the Effectiveness of Annual Free Health Screening Programs on Reducing the Risk of Occupational Diseases in Urban Areas of Indonesia - Iin Ira Kartika; Jumaedi; Wieke Widhiantika; Wendi Darmawan; Devi Fitriyastanti; Chaerunisa Tri Yuliana (Window of Health : Jurnal Kesehatan, 2026)
Occupational diseases remain a significant health issue in the industrial sector. According to the ILO, approximately 2.6 million deaths each year are caused by work-related diseases and accidents. Early detection and intervention through worker health screening are strategic steps to reduce the incidence of occupational diseases. However, the factors influencing the success of reducing occupational diseases remain under-researched. This study aims to identify factors associated with occupational diseases among workers using an analytical cross-sectional design. Data were collected from 258 industrial workers in Karawang Regency using a stratified random sampling method, and analyses were conducted using the chi-square test and logistic regression. A lower risk of occupational diseases was observed among respondents who participated in screening (OR=1.964; p=0.015), received quality screening services (OR=3.810; p=0.000), received early detection (OR=12.143; p=0.000), showed positive behavioral changes (OR=4.958; p=0.000), worked in large companies (OR=4.307; p=0.000), had good OSH knowledge (OR=1.892; p=0.014), and did not smoke (OR=4.558; p=0.000). The variables of screening follow-up (p=1.000) and OSH compliance (p=0.691) did not show a significant relationship. Increasing the implementation of occupational health screening could support efforts to prevent occupational diseases. This study provides an empirical basis for occupational health programs by emphasizing the importance of early detection, promoting healthy behavior, and preventing smoking as the main strategies.